Nerve ultrasound evaluation of Guillain‐Barré syndrome subtypes in northern China. Issue 5 (21st August 2021) - Liu, Li; Ye, Yuqin; Wang, Lijuan; Song, Xiaonan; Cao, Jie; Qi, Yajie; Xing, Yingqi
Abstract: Introduction/Aims: Ultrasound (US) studies have demonstrated patchy enlargement of spinal and peripheral nerves in Guillain‐Barré syndrome (GBS). However, whether ultrasound yields useful information for early classification of GBS has not been established. We aimed to evaluate nerve ultrasound in patients with GBS in northern China and compare the sonographic characteristics between demyelinating and axonal subtypes. Methods: Between November 2018 and October 2019, 38 hospitalized GBS patients within 3 wk of disease onset and 40 healthy controls were enrolled. Ultrasonographic cross‐sectional areas (CSA) of the peripheral nerves, vagus nerve, and cervical nerve roots were prospectively recorded in GBS subtypes and controls. Results: Ultrasonographic CSA exhibited significant enlargement in most patients' nerves compared with healthy controls, most prominent in cervical nerves. The CSA tended to be larger in acute inflammatory demyelinating polyneuropathy (AIDP) than in acute motor axonal neuropathy (AMAN)/acute motor and sensory axonal neuropathy (AMSAN), especially in cervical nerves (C5: 5.9 ± 1.6 mm 2 vs. 7.0 ± 1.7 mm 2, p = .042; C6: 10.5 ± 1.8 mm 2 vs. 12.0 ± 2.1 mm 2, p = .033). The chi‐squared test revealed significant differences in nerve enlargement in C5 ( p < .001), C6 ( p < .001), the proximal median nerve ( p < .001), and the vagus nerve ( p = .003) between GBS and controls. The vagus nerve was larger in patients with autonomic dysfunction than in patients without it (2.3 ± 1.0 mm 2 vs. 1.4 ± 0.5 mm 2, p = .003). Discussion: The demyelinating subtype presented with more significant cervical nerve enlargement in GBS. Vagus nerve enlargement may be a useful marker for autonomic dysfunction.